Pilgrimage to Wellness: Ayurveda’s Integral Role and Potential in Nepalese Tourism - Bhusal, Nirmal; Khanal, Bishnu Prasad; Acharya, Sunita; Ghimire, Bikas Raj (Nepalese Journal of Hospitality and Tourism Management, 2026)
Wellness tourism has emerged as one of the most rapidly growing travel industry recently. For tourism dependent countries and destinations worldwide, this has created both a challenge and an opportunity to reposition and diversify their offerings. This study aims to investigate the potential for integrating Ayurveda into Nepal’s tourism framework. This study utilizes a qualitative thematic analysis, to comprehensively investigate the potential for integrating Ayurveda wellness into Nepal’s tourism. The analysis reveals the deep historical roots of healing journeys in Nepal, from pilgrimage to herb trading, and current fragmented landscape of wellness provision. The findings indicate that Nepal possesses a authentic heritage, realizing its potential as a premier “Himalayan Wellness” destination. Wellness needs are personalized according to individual characteristics and personality traits. Programs that combine Ayurveda lifestyle (Dinacharya/ daily activities) - waking up at Brahma Muhurta (auspicious pre-dawn time), guided meditation, self-massage (Abhyanga), sessions on Sadvritta (truthfulness, contentment), mindful eating of Ayurveda meals, and Yoga Nidra experiences can add value to tourism. Establishing trust and authenticity to the tourists who are the clients is an immediate requirement to establish Ayurveda wellness tourism. To compete with established destinations, private and public sector must work together to establish a national system for Ayurveda tourism services that guarantees quality control.